Microcirculation and blood pressure/heart rate response during exercise stress testing in hypertensive patients. (3rd October 2022) - Liatakis, I; Konstantinidis, D; Tatakis, F; Drogkaris, S; Zamanis, I; Kariori, M; Polyzos, D; Siafi, E; Thomopoulos, C; Kakouri, N; Andrikou, I; Dimitriadis, K; et al.
Abstract: Background/Purpose: A hypertensive response during exercise has been associated with adverse cardiovascular outcomes in general population and hypertensive patients. On the other hand, microcirculation is the major site of control of vascular resistance and thus has a key role in the etiopathogenesis of hypertension. The aim of our study was to investigate the presence of a possible correlation between blood pressure and heart rate response during exercise with a microcirculation index (capillary rarefaction) in a cohort of hypertensive patients. Methods: We studied 105 untreated patients with stage I-II essential hypertension (70% men, mean age: 59.5 years, mean office blood pressure: 150/92mmHg). Patients with diabetes mellitus, secondary hypertension, atherosclerotic cardiovascular disease, heart failure, significant chronic renal or pulmonary disease and any other systemic illness or orthopedic problems that would not allow maximal effort on a treadmill were excluded. All participants underwent maximal exercise testing, using the Bruce protocol, as well as nail-fold videocapillaroscopy assessment by using VideoCap 3.0 videomicroscope. Results: A significant negative correlation between diastolic BP at minute-1 of the recovery phase and capillary density expressed in capillaries/mm was revealed (Pearson's r=−0.365, p=0.043). A significant negative correlation was also observed between capillary density and peak heart rate (Pearson's r=−0.364, p=0.024) as well as between heart rate increase from stage 1 to 2 and capillary density (Pearson's r=−0.746, p=0.013). Conclusions: Our study shows that in a small cohort of hypertensive patients, capillary rarefaction was associated with a steeper increase in heart rate during exercise, as well as with a higher peak heart rate and higher diastolic blood pressure values during the recovery phase. These findings suggest that new indices such as capillary rarefaction may provide insights into possible autonomic dysfunction and could also be taken into account in the assessment of hypertensive patients. Funding Acknowledgement: Type of funding sources: None.